Bring-Your-Own-Device (BYOD) practices in SMEs in Developing Countries – The Case of Tanzania - Kabanda, Salah; Brown, Irwin (ACIS, 2014)
BYOD is a practice that is manifest in most organizations; however few studies have looked at this phenomenon from a developing country perspective. This study reports on BYOD practices exhibited in Tanzanian SMEs. The paper follows a qualitative approach in which interviews and observation were the key data collection methods. The findings show that Tanzanian SMEs interpret BYOD as the use of a personal device to meet organizational needs regardless of whether the organizational network is being accessed or not. This was as a result of such SMEs not having ICT network infrastructure and resources. BYOD has been adopted by SMEs as a means of bypassing the investment required in organisational ICT resources. There was also a neglect of policy formulation for BYOD from SME management which posed a problem as employees became despondent that their personal devices were being used without due consideration to personal costs.